Foundations of health services research: principles, methods, and topics - Wensing, Michel; Ullrich, Charlotte (Springer, 2023)
Part 1: Introduction to Health Services Research -- Chapter 1. Description of Health Services Research -- Chapter 2. Fields of Health Services Research -- Part 2: Principles of Health Services Research -- Chapter 3. Use of Theories in Health Services Research -- Chapter 4. Scientific Integrity in Health Services Research -- Chapter 5. Presentation of Quantitative Research Findings -- Chapter 6. Dissemination and Utilisation of Research Findings -- Part 3: Research Methods in Health Services Research -- Chapter 7. Qualitative Methods in Health Services Research -- Chapter 8. Survey Methods in Health Services Research -- Chapter 9. Use of Electronic Patient Records for Health Services Research -- Chapter 10. Social Network Analyses in Health Services Research -- Chapter 11. Development and Validation of Questionnaires in Health Services Research -- Chapter 12. Development of Interventions -- Chapter 13. Process Evaluation in Health Services Research -- Chapter 14. Outcomes Evaluation in Health Services Research -- Chapter 15. Economic Evaluation in Health Services Research -- Chapter 16. Systematic Reviews of Healthcare Interventions -- Part 4: Emerging Topics in Health Services Research -- Chapter 17. Novel Interventions for Patient Empowerment -- Chapter 18. Mental Health Reform, Ecological Translation, and the Future of Public Mental Health Care -- Chapter 19. Dynamic Landscape of the Health Professions -- Chapter 20. Community Pharmacies as Healthcare Providers: New Developments in Medication Management and the Role of Information Technology -- Chapter 21. Continuity of Care: New Approaches to a Classic Topic of Health Services Research -- Chapter 22. Access to, Continuity and Coordination of Health Care for Refugees: Emerging Challenges and Topics for Health Services Research -- Chapter 23. Digital Technology for Information and Communication in Health Care -- Chapter 24. Climate Change as a Topic of Health Services Research.